The Relationship Between Work-Life Balance and Job Satisfaction Among Remote Workers (Universitas Kristen Indonesia Toraja, 2024)
Remote work has gained prominence in the modern workplace, raising concerns about work-life balance. This study investigates the relationship between work-life balance and job satisfaction among remote workers. Survey data from 500 respondents reveal that flexibility and time management significantly influence job satisfaction, providing insights for remote work policies.